2016
DOI: 10.1002/ijc.30394
|View full text |Cite
|
Sign up to set email alerts
|

FANCM c.5101C>T mutation associates with breast cancer survival and treatment outcome

Abstract: Breast cancer (BC) is a heterogeneous disease, and different tumor characteristics and genetic variation may affect the clinical outcome. The FANCM c.5101C > T nonsense mutation in the Finnish population associates with increased risk of breast cancer, especially for triple‐negative breast cancer patients. To investigate the association of the mutation with disease prognosis, we studied tumor phenotype, treatment outcome, and patient survival in 3,933 invasive breast cancer patients, including 101 FANCM c.5101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Although recent works established a link between the heterozygous c.5101C>T FANCM truncating mutation and BOC predisposition in the Finnish population ( Kiiski et al, 2016 , 2014 ; Neidhardt et al, 2017 ), there is no history of BOC in the family investigated here. Interestingly, a few apparently healthy (i.e., without cancer) individuals homozygous for the c.5101C>T FANCM mutation were identified in previous studies ( Kiiski et al, 2016 , 2014 ; Neidhardt et al, 2017 ). Indeed, the authors stated, by direct observation or by looking at registered clinical data, that none of them presented FA stigmata (although no data on age, sex or clinical findings was made available).…”
Section: Discussionmentioning
confidence: 64%
“…Although recent works established a link between the heterozygous c.5101C>T FANCM truncating mutation and BOC predisposition in the Finnish population ( Kiiski et al, 2016 , 2014 ; Neidhardt et al, 2017 ), there is no history of BOC in the family investigated here. Interestingly, a few apparently healthy (i.e., without cancer) individuals homozygous for the c.5101C>T FANCM mutation were identified in previous studies ( Kiiski et al, 2016 , 2014 ; Neidhardt et al, 2017 ). Indeed, the authors stated, by direct observation or by looking at registered clinical data, that none of them presented FA stigmata (although no data on age, sex or clinical findings was made available).…”
Section: Discussionmentioning
confidence: 64%
“…In the Finnish population, p.Gln1701* was found to be associated with breast cancer risk with an odds ratio (OR) of 1.86 and with greater effects in familial cases, and for estrogen receptor-negative (ER-negative) and triple-negative breast cancer (TNBC) subtypes [5]. This variant was later found to be also associated with breast cancer survival and treatment outcome [6]. A second FANCM PTV, the c.5791C > T (p.Gly1906Alafs12*, rs144567652), which is annotated and hereafter referred to as p.Arg1931*, showed association with breast cancer risk in familial cases with OR = 3.93 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The two most common FANCM variants we observed are more common in European populations than other world populations. These variants were both first identified in European ancestry BRCA1/2-negative familial breast cancer studies, 46,47 and both have previously been associated with ER-negative or triple negative breast cancer. 46,48,49 Additionally, rs147021911 (chr14:45658326C>T, c.5101 C >T, p.Gln1701*) was associated with poor breast cancer survival in a Finnish population, 50 and other FANCM LoF mutations were found in small breast cancer case series, [51][52][53][54][55] including a study that showed bi-allelic FANCM variants in early onset or bilateral breast cancer cases.…”
Section: Discussionmentioning
confidence: 94%